2021
DOI: 10.12731/2658-6649-2021-13-3-208-224
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mineral Nutrient Impact on Metabolites Accumulation in Kale (Brassica Oleracea Var. Sabellica)

Abstract: Green leafy kale (Brassica oleracea var. sabellica) has huge scientific attention because of its health-promoting functionality. In the present study the impact of NPK, energen, biostim and humate on flavonoid, phenolic compounds, vitamin C, carotenoids, malondialdehyde (MDA), protein, proline and soluble sugar in kale was investigated. The mineral nutrients mostly increased but in some cases maintained the studied metabolites. The stimulatory effect of applied mineral nutrients on the phytochemicals analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Some studies have shown that the treatment of plants with solutions and mixtures of mineral salts such as NPK increased the accumulation of polyphenolic compounds several times over in comparison with test plants [16,17]. On the other hand, there is evidence of a significant decrease in the amount of soluble phenolic compounds and flavonoids in different plants under the influence of NPK [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the treatment of plants with solutions and mixtures of mineral salts such as NPK increased the accumulation of polyphenolic compounds several times over in comparison with test plants [16,17]. On the other hand, there is evidence of a significant decrease in the amount of soluble phenolic compounds and flavonoids in different plants under the influence of NPK [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…where C is the amount of MDA (mmol/g dry weight); ΔD is the difference in optical density of the sample at 532 and 600 nm; 155 -extinction coefficient of MDA at 532 nm, mM -1 cm -1 ; X -dilution, i.e. the total volume of the reaction mixture was divided by the amount of the introduced extract sample; V -the volume of the extract (mL); m -the mass of the wet sample (g); Δm -the ratio of dry and wet weight; 1 -optical path length (cm) (Anteh et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of vitamin C was determined using a calibration curve. The vitamin C content was calculated using the formula: C = (K * V * X)/(m * Δm * L), where C is the content of vitamin C (μg/g wet weight); K -the concentration of vitamin C (μg/mL); V -the total volume of the extract (mL); X -the dilution of the extract in the reaction mixture; L -the length of the optical path (cm); m -the mass of the wet sample (g); Δm -the ratio of dry weight to wet weight (Anteh et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [20], deep reinforcement model was applied for crop yield prediction. Spectrophotometric methods were introduced in [21] to improve the quality of natural sources. Environmental and economic efficiency protective afforestation was introduced in [22] to achieve the quality of soil and climatic conditions.…”
Section: Introductionmentioning
confidence: 99%